Serotype distribution of invasive pneumococcal disease from countries of the WHO Africa, Americas, Eastern Mediterranean, South-East Asia, and Western Pacific regions: a systematic literature review from 2010 to 2021 - Fletcher, Mark A.; Daigle, Derek; Siapka, Mariana; Baay, Marc; Hanquet, Germaine; del Carmen Morales, Graciela (Frontiers in Public Health, 2024)
Background: Most publications on invasive pneumococcal disease (IPD) serotype distribution are from about 20 countries (Australia, Canada, China, European Union members, Japan, New Zealand, South Korea, and USA). Here, we reviewed the literature among underrepresented countries in the Americas (AMRO), Africa (AFRO), Eastern Mediterranean (EMRO), South-East Asia (SEARO), and Western Pacific (WPRO) WHO regions. Methods: We performed a systematic review of the most recent IPD serotype surveillance publications (from 01/01/2010 to 31/12/2021, Medline/Embase) in those WHO regions. Selection criteria were delineated by contemporality, within-country geographical scope, and number of samples. Reported serotype distributions for each country were stratified by age group, pneumococcal conjugate vaccine (PCV) serotype category (considering undifferentiated serotypes), and PCV program period (pre-PCV, intermediate, or PCVhv [higher valency PCV formulation]). Pre-PCV period pooled data estimated PCV serotype category distribution by age group across WHO regions, while for the PCVhv period, country-level dataset tables were prepared. Results: Of 2793 publications screened, 107 were included (58 pediatric, 11 adult, 37 all ages, and one comprising every age group). One-third of eligible countries (51/135) published serotype distribution, ranging from 30-43% by WHO region. Considering number of samples per WHO region, a few countries prevailed: AMRO (Brazil), AFRO (South Africa, Malawi, and Burkina Faso), and WPRO (Taiwan). In the pre-PCV period, PCV13 formulation serotypes predominated: ranging from 74-85% in children and 58-86% in adults in the different WHO regions. The PCVhv period represented half of the most recent IPD surveillance, by publications (49/107) or countries (25/51). Undifferentiated serotypes represented >20% of IPD from most countries (34/51). Conclusion: Ubiquity of undifferentiated serotypes among the publications could constrain estimates of PCV program impact and of serotype coverage for newer PCVhv formulations; consequently, we recommend that countries favor techniques that identify serotypes specifically and, rather than reporting PCV formulation serotype distributions, provide serotype results individually.